Laminar Mixed Convection in Inclined Triangular Enclosures Filled with Water Based Cu Nanofluid - Rahman, M. M.; Öztop, Hakan Fehmi; Ahsan, A.; Saidur, R.; Al-Salem, Khaled; Rahim, N. A. (Amer Chemical Soc, 2012)
This paper presents the results on mixed convection in an inclined lid-driven triangular enclosure filled with water based Cu nanofluid. The enclosure is cooled at the inclined surface and simultaneously heated at the base surface. The vertical wall is adiabatic and moving at a constant speed. The governing equations are solved numerically by the Galerkin finite element method. The effects of parameters such as the Richardson number, nanoparticle volume fraction, and tilt angle on the flow and thermal fields as well as the heat transfer rate of the heated surface are taken into account. The overall heat transfer rate of the heated surface is characterized by the average Nusselt number at the heated surface. It has been observed that the effects of the tilt angle and solid volume fractions are significant on the flow and thermal fields. Besides, an optimum value for the solid volume fraction is found, which results in the maximum heat transfer rate at the considered values of the Richardson numbers. The rate of the increase of the average Nusselt number is slow for higher values of the tilt angle while it is much quicker for lower values of the tilt angle.
Keywords: Unsteady Natural-Convection; Heat-Transfer Enhancement; Finite-Element-Analysis; Flow